Analisis Partisipasi Masyarakat dalam Pelaksanaan Musyawarah Perencanaan Pembangunan Desa di Desa Pulau Semambu, Ogan Ilir - Rafinzar, Rahmat; Mardianto, Mardianto (Jurnal Publisitas, 2023)
This research aims to find out how the community participates in the implementation of the musrenbangdes in Pulau Semambu village, North Indralaya sub-district, Ogan Ilir Regency. The problems found in the implementation of Musrenbang in Pulau Semambu village were a lack of community understanding and minimal community involvement in the process of organizing Musrenbangdes. The theoretical reference used in this research is based on the theory of community participation according to Cohen and Uphoff. Research data was collected by means of observation, interviews, documentation and literature study which was then analyzed using descriptive qualitative methods. The research results show that community participation in decision making shows that the community is still less active and believes that the musrenbangdes is a formality agenda. Then, participation in implementation shows that the community is making contributions to support development implementation. In the aspect of Participation in benefits, budget limitations are a problem that results in the non-fulfillment of some of the village needs proposed by the community. Then Participation in evaluation shows that community involvement in monitoring and providing assessments of the results of planning through open dialogue is still minimal.